ANALISIS KESULITAN BELAJAR DAN FAKTOR-FAKTOR PENYEBAB KESULITAN BELAJAR IPA SISWA KELAS IV B SD NEGERI MEDANG: Jurnal Skripsi - Septi Bela Diani; Harlinda Syofyan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Science is one of knowledge which is learned about events and problems on earth. Science is the most important knowledge because science has benefits and can be used in daily activities. Based on this, science material must be taught from elementary school..but in learning science in elementary schools, students still struggle when understanding the course. The research was conducted in grade IV B in Medang Elementary School by using qualitative methods which aim to find out factors that cause learning difficulties in students on science subjects in grade IV B in Medang Elementary School. The results of this research show most of the students grade IV B in Medang Elementary School have learning difficulties on science subjects. The factors which cause learning difficulties on science subjects are divided into two categories, there are factors internal and external. Factors internal including mental maturity, intelligence, interest and motivation. Whereas factors external including family environment, community environment, teacher and media instrumental. Both of these factors have a very important role in improving the quality of learning outcomes.